Do EU Funds Crowd Out Other Public Expenditures? Evidence on the Additionality Principle from the Detailed Czech Municipalities' Data - Petr Jansky; Tomas Krehlik; Jiri Skuhrovec (Charles University in Prague, Institute of Economic Studies (IES), 2016)
European Union funds flowing into budgets of public sector organisations of its member states should be additional to their nationally funded expenditures. To investigate this additionality principle systematically, we develop a new empirical method. Our main hypothesis is that some of the EU-funded projects are crowding out national public expenditures. Not being able to reject the hypothesis would be consistent with violating the additionality principle. To test the hypothesis we examine how EU funding translates into actual spending of relatively comparable municipalities of the Czech Republic. We innovatively match the municipal authorities' budgetary data on EU-funded expenditure projects with their other, nationally funded, expenditures. We find no systemic crowding out of national public expenditures by EU funds at the level of operational programmes in the Czech municipalities' data, which is consistent with no evidence of violating the additionality principle. Nonetheless, going down to the municipal level enable us to show how the results can pinpoint individual cases of EU fund's potential mismanagement in Czech municipalities. Overall, we provide the first evaluation of the additionality principle at the level of individual recipients of EU funds and in doing so we develop a methodological approach potentially applicable to other fund recipients.
Keywords: 330; European Union; EU Cohesion policy; EU funds; crowding out; additionality; municipalities